2016
DOI: 10.1021/acsami.6b00106
|View full text |Cite
|
Sign up to set email alerts
|

A High-Performance Rechargeable Mg2+/Li+ Hybrid Battery Using One-Dimensional Mesoporous TiO2(B) Nanoflakes as the Cathode

Abstract: . (2016). A high-performance rechargeable Mg2+/Li+ hybrid battery using one-dimensional mesoporous TiO2(B) nanoflakes as the cathode. ACS Applied Materials and Interfaces, 8 (11),[7111][7112][7113][7114][7115][7116][7117] A high-performance rechargeable Mg2+/Li+ hybrid battery using onedimensional mesoporous TiO2(B) nanoflakes as the cathode AbstractMg2+/Li+ hybrid batteries have recently been constructed combining a Mg anode, a Li+-intercalation electrode, and an electrolyte containing both Mg2+ and Li+. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 40 publications
2
43
0
Order By: Relevance
“…Considering that the redox potential of Mg 2+ /Mg is 0.67 V higher than that of Li + /Li, the voltage window of LIB was limited between 0. used in the MRB and MLIB. [29] It can be seen from Figure S4a (Supporting Information) that the GF hardly delivered any capacity in the MRB, indicating GF is almost electrochemically inactive toward Mg 2+ . Figure S4b (Supporting Information) shows that the capacity of the GF electrode in the LIB cell was below 20 mA h g −1 , much lower than that of graphite.…”
Section: Electrode Performancementioning
confidence: 99%
“…Considering that the redox potential of Mg 2+ /Mg is 0.67 V higher than that of Li + /Li, the voltage window of LIB was limited between 0. used in the MRB and MLIB. [29] It can be seen from Figure S4a (Supporting Information) that the GF hardly delivered any capacity in the MRB, indicating GF is almost electrochemically inactive toward Mg 2+ . Figure S4b (Supporting Information) shows that the capacity of the GF electrode in the LIB cell was below 20 mA h g −1 , much lower than that of graphite.…”
Section: Electrode Performancementioning
confidence: 99%
“…Strategies to improve the kinetics, i.e., new synthetic ways for electrode materials, are therefore necessary for the development of multivalent ion battery materials. Few studies have reported the use of TiO 2 or its composites as cathode materials for Mg‐ion batteries and hybrid Mg/Li batteries . However, the extension of these studies toward anodically grown NTs has still to be realized.…”
Section: Use Of Tio2 Nanotubes In Multivalent Ion Batteriesmentioning
confidence: 99%
“…This marked the discovery of the first stable, halide-free electrolyte for magnesium batteries. Since then, there have been a number of experimental 13,[20][21][22][23][24][25] and theoretical 12,23,26 studies aimed at improving battery performance. Presently, there are some problems with this electrolyte, including low ionic conductivity and solubility.…”
mentioning
confidence: 99%